A Metacognitive Model of Writing: An Update From a Developmental Perspective. Issue 4 (2nd October 2018) - Hacker, Douglas J.
Abstract : In this article, writing is reconceptualized as primarily a metacognitive process that can be modeled using contemporary metacognitive theory. This reconceptualization of writing was described in an earlier publication, but in the current article the author provides an update on this metacognitive model of writing with 3 purposes in mind. First, the model is elaborated by using a broad range of literature from metalinguistics and children's writing development that includes a strong focus on the nature of written language. Second, a developmental perspective on the model is provided. Third, future research stemming from this model of writing is discussed, with an emphasis on children's use of writing as a way to instruct reading and on the use of metalinguistics and metapragmatics to develop writing skills.